2005
DOI: 10.1200/jco.2005.02.3739
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study of Second-Line Chemotherapy for Advanced Non–Small-Cell Lung Cancer With Weekly Compared With 3-Weekly Docetaxel

Abstract: Weekly docetaxel 35 mg/m2 demonstrated similar efficacy and better tolerability than standard 3-weekly docetaxel 75 mg/m2 and can be recommended as a feasible alternative second-line treatment option for patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 18 publications
12
110
4
1
Order By: Relevance
“…In particular, the present trial confirms our previous observation (Tibaldi et al, 2006) that a modified schedule of docetaxel (37.5 mg m À2 on days 1 and 8 every 3 weeks) is feasible and well tolerated in elderly advanced NSCLC patients. Our tolerability data confirm the previous observations that weekly docetaxel is advantageous in terms of haematological toxicity with respect to 3-weekly schedule (Gridelli et al, 2004;Schuette et al, 2005;Camps et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In particular, the present trial confirms our previous observation (Tibaldi et al, 2006) that a modified schedule of docetaxel (37.5 mg m À2 on days 1 and 8 every 3 weeks) is feasible and well tolerated in elderly advanced NSCLC patients. Our tolerability data confirm the previous observations that weekly docetaxel is advantageous in terms of haematological toxicity with respect to 3-weekly schedule (Gridelli et al, 2004;Schuette et al, 2005;Camps et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…Three randomised phase III trials (Gridelli et al, 2004;Schuette et al, 2005;Camps et al, 2006) have compared, in second line advanced NSCLC, docetaxel at the dose of 75 mg m À2 every 3 weeks, considered the standard of care, against a weekly schedule, indicating a similar efficacy but a significantly less severe toxicity in terms of leukopenia, neutropenia and febrile neutropenia with weekly docetaxel.…”
mentioning
confidence: 99%
“…In conclusion, the results of four randomized trials [13][14][15][16] and two meta-analyses [17,18] demonstrate no difference in survival, although there are some critical issues because of the limited number of patients (about 700) and the different endpoints considered (safety, overall survival, quality of life) that mean that no clear, conclusive definition of the role of a weekly docetaxel schedule can be determined. The use of a weekly docetaxel schedule for relapsed NSCLC patients is not supported by a direct comparison with pemetrexed.…”
Section: Single-agent Weekly Docetaxelmentioning
confidence: 99%
“…In a German study [15], 208 patients were randomized to receive 3-weekly or weekly docetaxel (35 mg/m 2 for 3 weeks every 28 days), and the primary endpoint was overall survival. A significantly lower rate of hematologic toxicity was recorded for the weekly arm (20.6% versus 4.8% patients suffered from neutropenia), with a significant difference observed in the median survival time and 1-year survival rate for the two schedules (6.3 versus 9.2 months and 26.9% versus 39.5% in the 3-weekly and weekly treatment groups, respectively; p = .07).…”
Section: Single-agent Weekly Docetaxelmentioning
confidence: 99%
“…In studies of nonsmall-cell lung cancer patients, weekly use of docetaxel signiWcantly reduced hematologic toxicity without compromising eYcacy [8,9]. Several studies on colorectal cancer reported low incidences of toxicities for weekly 5-FU administration [10,11].…”
Section: Introductionmentioning
confidence: 99%